Innovation, Territory and industrial development in Portugal - Fonseca, Maria Lucinda; Gaspar, Jorge; Vale, Mário (Finisterra, 1996)
Innovation holds an important role in the economic development process. The competitive potential of national and regional economies is based on the ability to manage the changing technological process. Economic competition does no longer exclusively depend on the factor costs, which vary geographicaly, because technology can now eliminate the territory disadvantages. Productivity is the crucial element in the competitive capacity of any economy. Productivity, as can easily be proved, is deeply dependent on technological development; this is only possible if there is constant innovation. This paper starts with a brief discussion on the theoretical issues regarding innovation in relation to regional economies. In the second section the Portuguese R&D system is analised in terms of finance and human resources. Particular attention is paid to the entrepreneurial R&D effort, namely in manufacturing activity. Finally, some limitations of the innovation policy in the EU are pointed out, together with its consequences for the least favoured regions.